ANALISIS PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - I Made Purba Astakoni; Wiryawan Suputra Gumi (Forum Manajemen STIMI Handayani Denpasar, 2017)
The purpose of this study are (1) to analyze the effect of the physical work environment on job satisfaction of employees at the Department of Culture in Denpasar; (2) To analyze the effect of the physical work environment on the performance of employees at the Department of Culture of Denpasar; (3) To analyze the effect of job satisfaction on the performance of employees at the Department of Culture in Denpasar; (4) To elucidate the role of job satisfaction in mediating the effects of the physical work environment on the performance of employees at the Department of Culture of Denpasar. Total population in this study were as many as 30 employees of the Department of Culture of Denpasar. Given the population is only 30 people, the entire population sampled and thus this study is a study with a sample saturated. In this study, analysis of data using the approach Partial Least Square (PLS). Based on hypothesis testing found that the physical work environment is positive and significant impact on job satisfaction means that the better the physical work environment also increase the job satisfaction of physical labor. Physical work environment positive and significant effect on employee performance. Research has found job satisfaction and significant positive effect on employee performance. Based on the results of research mediating role of job satisfaction on the physical work environment on employee performance showed that job satisfaction partially tested as mediating variables (Parthials Mediation) between the physical work environment on employee performance.